Morchella esculenta cultivation in fallow paddy fields and drylands affects the diversity of soil bacteria and soil chemical properties - Duan, Mingzheng; Yang, Chengcui; Bao, Liuyuan; Han, Duo; Wang, Huaizheng; Zhang, Yongzhi; Liu, Honggao; Yang, Shunqiang (Frontiers in Genetics, 2023)
The properties of paddy field (DT) and dry land (HD) soil and food production can be enhanced by the cultivation of Morchella esculenta (ME) during the fallow period. However, whether ME cultivation affects the soil health and microbial diversity of paddy fields and drylands during the cultivation period remains unclear, and this has greatly limited the wider use of this cultivation model. Here, we analyzed the soil chemical properties and bacterial diversity (via metabarcoding sequencing) of DT and HD soils following ME cultivation. Our findings indicated that ME cultivation could enhance soil health. The content of soil phosphorus and potassium (K) was increased in DT soil under ME cultivation, and the K content was significantly higher in HD soil than in DT soil under ME cultivation. ME cultivation had a weak effect on alpha diversity, and ME cultivation affected the abundance of some genera of soil bacteria. The cultivation of ME might reduce the methane production capacity of DT soil and enhance the nitrogen cycling process of HD soil based on the results of functional annotation analysis. Network analysis and correlation analysis showed that Gemmatimonas, Bryobacter, and Anaeromyxobacter were the key bacterial genera regulating soil chemical properties in DT soil under ME cultivation, and Bryobacter, Bacillus, Streptomyces, and Paenarthrobacter were the key taxa associated with the accumulation of K in HD soil. The results of our study will aid future efforts to further improve this cultivation model.